2013
DOI: 10.1177/1352458513499420
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of deep gray matter lesions on magnetic resonance imaging among adults with acute disseminated encephalomyelitis, multiple sclerosis, and neuromyelitis optica

Abstract: Morphological features of deep gray matter lesions vary among adult patients with ADEM, MS, and NMO, and may be helpful in distinguishing these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…The conventional MRI protocols were described in our previous paper (Zhang et al., 2014). Gadopentate dimeglumine (Gd‐DTPA) was intravenously administered at a dose of 0.1 mmol/kg, and at about 15 min after contrast injection, the T1‐weighted sequence was repeated.…”
Section: Methodsmentioning
confidence: 99%
“…The conventional MRI protocols were described in our previous paper (Zhang et al., 2014). Gadopentate dimeglumine (Gd‐DTPA) was intravenously administered at a dose of 0.1 mmol/kg, and at about 15 min after contrast injection, the T1‐weighted sequence was repeated.…”
Section: Methodsmentioning
confidence: 99%
“…82,83 Though ADEM is often monophasic, recent studies reported that relapses can occur in 10–18% of cases. 44,84,85 ADEM can manifest as LETM, bilateral multiple cerebral lesions of the white matter, 86 bilateral optic neuritis, 87 or deep gray matter lesions, 88 all of which can be seen in NMOSD. 1 Moreover, a considerable number of patients diagnosed with ADEM in clinical practice did not meet the current diagnostic criteria for ADEM, 84 highlighting the difficulties in defining ADEM.…”
Section: Differential Diagnosis Of Nmosdmentioning
confidence: 99%
“…Brain MRI abnormalities have been reported in previous studies in patients with NMO [6][7][8][9][10][13][14][15]. However, few studies have focused on effects of brain MRI abnormalities on NMO.…”
Section: Discussionmentioning
confidence: 93%